The Impact of University Governance on the Quality of Educational Process in both of Basra University and the Southern Technical University: A Field Study - Alawi , Muslim; Mohsin, Abdulridha (The Arab Journal of Administration, 2020)
The Iraqi Ministry of Higher Education is trying to develop a broad and effective governance system, for improvement the educational process of its universities, because this system ensures the quality improvement of educational process, and could be able to provide further improvement, by consistent with improvement continuous process in the higher education sector, This will undoubtedly contribute to providing opportunities to ensure further improvement in the concepts and practices of managing universities and colleges , especially in Iraqi universities and colleges, which still need to self-control systems, and official systems that ensure full compliance for implementation of quality improvement requirements in higher education, , This requires the availability of wise and fair leadership on the one hand, and ensuring compliance with the principles of transparency, independence of responsibility, participation , and accountability on the other hand , therefore, the main objective of the research was to reveal the impact of universities governance by all that means (values and ethics) in improving the comprehensive educational process at the University of Basra, And the Southern Technical University , Because the outputs of the educational process (students and research) are describing the service provided by the university to the community (i.e., the university’s mission).The research adopted a main hypothesis that (there is impact with a statistical significance of the independent variable (the universities governance and their sub- variables) On the depend variable) Quality performance of the educational process). The field study was determined at Faculty of Administration and Economics at the University of Basra and the Technical College at the Southern Technical University. The most important reasons are: Continuous presence of researchers in these colleges helps to identify directly the problems in the implementation of quality improvement systems, - and they correspond to the same administrative competence of researchers, - as well as these colleges attempts to implement quality management systems.), The research attempted to reach its main goals by using two methods: The first method is aims to reveal the extent to which administrative and academic bodies in higher education are aware of the universities governance , and the extent to which they can be used this governance in Iraqi universities and colleges, the second method is the search for the causal relationship between universities governance, described by its main variables, and indicators that measure the performance of the educational process. The search was used for data collection two method, the first is a checklist to collect data that reveals Orienting and understanding of administrations to the concepts of universities governance and its implementation mechanisms, and the second is questionnaire to reveal the causal relationship between university governance and improving the educational process. The research reached to set of results, the most important of which is the positive role of university governance in improving the educational process in light of the availability of the appropriate environment.